KEADILAN DAN HAM DALAM PERLINDUNGAN PEKERJA MIGRAN MENURUT HUKUM ISLAM - Syapar Alim Siregar; Agustina Damanik; Iskandar (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2026)
Migrant workers constitute one of the vulnerable groups frequently exposed to exploitation, discrimination, and violations of human rights, both in their countries of origin and in destination countries. In the Indonesian context, various cases involving violence, unpaid wages, and weak legal protection demonstrate the urgent need to strengthen safeguards for migrant workers. This article aims to analyze the protection of migrant workers from the perspective of Islamic law by emphasizing the principles of justice, humanity, and respect for human rights. The research employs a normative juridical method with a descriptive qualitative approach, through an examination of relevant Qur’anic verses, hadith, and fiqh literature, as well as a comparison with international legal instruments. The results of the analysis indicate that Islam emphasizes the importance of fair treatment of workers, the obligation of employers to provide decent wages, and the protection of human dignity as a mandate of Sharia. These principles are in line with international standards and, therefore, may serve as a normative and ethical basis for strengthening policies on the protection of migrant workers.